2017
DOI: 10.1038/onc.2017.258
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity and heterogeneous acquired resistance of combined MDM2 and MEK inhibition in KRAS mutant cancers

Abstract: There are currently no effective targeted therapies for KRAS mutant cancers. Therapeutic strategies that combine MEK inhibitors with agents that target apoptotic pathways may be a promising therapeutic approach. We investigated combining MEK and MDM2 inhibitors as a potential treatment strategy for KRAS mutant non-small cell lung cancers and colorectal carcinomas that harbor wild-type TP53. The combination of pimasertib (MEK inhibitor) + SAR405838 (MDM2 inhibitor) was synergistic and induced the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 56 publications
4
30
0
Order By: Relevance
“…This indicates that MV4-11 and OCI-AML-2 contain pre-existing TP53 -mutant subpopulation that are selected by nutlin-3 treatment, while nutlin-3 treatment resulted in de novo TP53 mutations in OCI-AML-3 and SIG-M5. These results are consistent with those obtained from other cancer entities [35,36,39,41].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates that MV4-11 and OCI-AML-2 contain pre-existing TP53 -mutant subpopulation that are selected by nutlin-3 treatment, while nutlin-3 treatment resulted in de novo TP53 mutations in OCI-AML-3 and SIG-M5. These results are consistent with those obtained from other cancer entities [35,36,39,41].…”
Section: Resultssupporting
confidence: 92%
“…MDM2 inhibitors are currently being investigated in phase II and III clinical trials for AML (NCT02670044, NCT02545283). In various cell types, resistance formation to MDM2 inhibitors has previously been shown to be associated with the selection of pre-existing TP53 -mutant cancer cell populations or the induction of de novo TP53 mutations [3,35,36,39,41]. A clinical trial in liposarcoma patients confirmed that MDM2 inhibitor therapy is also associated with the emergence of TP53 mutations in the clinic [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance can occur by selection of pre-existing drug-resistant subpopulations or by adaptation of originally drug-sensitive cells to anti-cancer therapies. Both mechanisms have been shown to be represented in drug-adapted cancer cell lines [52,[66][67][68][69][70][90][91][92][93][94][95][96][97][98][99][100][101] .…”
Section: Multiple Resistance Models Are Needed To Reflect the Heterogmentioning
confidence: 99%
“…Acquired resistance mechanisms are still not understood, especially in glioblastoma. Potential mechanisms leading to acquired MDM2 inhibitor resistance are p53 mutations (21)(22)(23)(24) as well as enhanced B-cell lymphoma-extra-large (Bcl-xl) or MDM4 protein expression, offering the opportunity to be targeted by the addition of specific inhibitors (25).…”
Section: Introductionmentioning
confidence: 99%